Manifestations and Causes of Altruism in Animals - Uchmański, Janusz; Niczyporuk, Sylwia (Studia Ecologiae et Bioethicae, 2021)
The aim of the paper is to provide an evolutionary explanation for co-operation and altruism in the animal world, together with other forms of intra- and inter-species relationships, which bring benefits for both sides involved in it. Concepts of individual selection, group selection, and kin selection were used. The work emphasises the relevance of intra-specific and inter-species relations, in shaping the image of nature. During the analysis of intra-specific interactions, it is explained how the degree of kinship affects the relations between relatives, and what are the results of it, regarding the degree of kinship. The article discusses the notion of kin selection, providing numerous examples in this area. Furthermore, it explains the concept of Hamilton’s rule, which covers these phenomena in a quantitative way. Whilst analysing the possibility of co-operation between non-related individuals of the same species, the authors introduce the notion of reciprocal altruism, and explain a particular way of thinking about the above problems, called the ‘prisoner’s dilemma’. Possible changes that may appear during co-evolution between different species, have also been considered. Examples of co-operation between species that rely on the construction of ecological niches were provided. It has especially been wondered if co-evolution can lead to increased intensity of positive relations between species, up to the manifestations of inter-species altruism inclusive.